Effectiveness and feasibility of a joint attention (JA)-based parent-mediated intervention (PMI) for Malaysian children with autism spectrum disorder (ASD): cultural considerations - Chee, Zia Wei (2021)
Background Social interaction and social cognition models underpinning joint attention (JA)-based parent-mediated interventions (PMIs), advocate family-centred practices and child-directed interactions as current best practices for autism spectrum disorder (ASD) early language intervention. PMIs place emphasis on Speech-language Therapist (SLT)-parents partnership. Parents are coached to become co-therapist by learning and applying a series of interaction and language facilitation strategies, aimed to enhance parent-child interactions and support their children’s JA, language, and social communication development. While the effectiveness of PMIs is mainly grounded on evidence from Western and high-resource countries, the effectiveness of PMIs in other cultures is unknown.